Social and fiscal impacts of statutory minimum wages in EU countries: A microsimulation analysis with EUROMOD - Klaus Grünberger; Edlira Narazani; Stefano Filauro; Áron Kiss (European Commission, Joint Research Centre (JRC), 2021)
This paper analyses the first-round effects of hypothetical minimum wage increases on social outcomes in 21 EU countries with a statutory national minimum wage based on a microsimulation approach using EUROMOD. The methodological challenges related to the use of available EU household survey data are described, along with the choices made to address these challenges. The paper assesses hypothetical scenarios in which countries with a statutory national minimum wage increase their minimum wage to various reference values, set in relation to the gross national median and average wage. The model simulations suggest that minimum wage increases can significantly reduce in-work poverty, wage inequality and the gender pay gap, while generally improving the public budget balance. The implied wage increases for the beneficiaries are substantial, while the implied increases in the aggregate wage bill and, as a consequence, possible negative employment impacts, are generally modest.
Keywords: H31; I32; J31; 330; minimum wage; microsimulation; European Union; wage inequality; in-work poverty; gender pay gap